Strategi Manajemen Pembelajaran pada Masa Covid-19 di SMK Ma’arif 9 Kebumen - Agus Nur Soleh . (LPPM IAINU Kebumen, 2020)
The writing of this scientific work is the result of collaborative research on Curriculum Management and Learning in the Covid-19 Period at Ma'arif 9 Vocational School, Kebumen. This study aims to determine curriculum and learning management during the Covid-19 period. The formulation of the problem in this article is (1) How is the management of curriculum and learning during the Covid-19 period at Ma'arif 9 Kebumen Vocational School? (2) What are the results of the SWOT analysis on curriculum management and learning management at SMK Ma'arif 9 Kebumen? This study used a qualitative research method with interview, observation, and documentation techniques as well as a SWOT analysis which was carried out on July 20-24 2020 at Ma'arif 9 Vocational School, Kebumen. Informants from this study included school principals, deputy heads of curriculum, and heads of departments. The results of this study are that Ma'arif 9 Kebumen Vocational School continues to use the same curriculum as before the pandemic occurred, namely the 2013 curriculum. Although there have been some changes in the learning process, where the learning process which used to use the face-to-face method was changed with several methods to adjust health protocols including online methods, and so on.